The Mediating Role of Organizational Citizenship Behavior on the Effect of Passion and Empowerment on Job Performance - Amalia, Prima Rizka; Wahyuningsih, Sri Handari; Surwanti, Arni (Jurnal Manajemen Bisnis, 2021)
Research aims: This research aims to analyze the mediating role of organizational citizenship behavior (OCB) on the effect of passion and empowerment on teachers' job performance.Design/Methodology/Approach: Respondents in this research were Muhammadiyah elementary school teachers in Ngampilan and Wirobrajan Districts. This research used nonprobability purposive judgment sampling with the number of respondents as many as 51 teachers. Statistical tests and data processing were then carried out utilizing the Partial least Square (SmartPLS) 3.0.Research findings: The research found that passion had a positive and significant effect on organizational citizenship behavior. This research also revealed that organizational citizenship behavior and empowerment positively and significantly affected job performance, while passion was significant toward job performance with partial mediation of organizational citizenship behavior.Theoretical Contribution/Originality: OCB serves as a mediating variable in this analysis, while in previous studies, these variables were not mediated by OCB.Practitioners/Policy Implications: As a result, the principal must enable teachers to be flexible in their teaching and learning activities. Teachers must also be active in voluntary activities outside of teaching and learning that can enhance their abilities and skills to improve their performance.Research Limitations/Implications: The study was only performed at Muhammadiyah elementary schools in Ngampilan and Wirobrajan Districts. Therefore, the collected data had a low degree of normality.